Investigating The Relationship Between Midwifery Students’ View on Traditional/Complementary Medicine and Health Perception: A Descriptive Study - Sümeyye BAL; Emine Koç; Onur ÖZTÜRK (KHD-Production, 2022)
Introduction: This study aimed to investigate the relationship between the view of midwifery students on complementary and alternative medicine (CAM) practices and their health perception. Methods: This cross-sectional study was conducted in the midwifery department of the Faculty of Health Sciences of a university in the Black Sea Region between October 4th and November 22nd, 2021 (n=304). Descriptive information form, Complementary, Alternative and Conventional Medicine Attitude Scale (CACMAS), and Health Perception Scale were used to collect the data. SPSS 23.0 statistical program was used for conducting data analysis and the data were presented using mean, standard deviation, number, and percentage values. Correlation analysis was performed to investigate the relationship between the variables. Results: A total of 304 female students participated in this study with a mean age of 20.98 ± 2.18 years. Among them, 68.4% of the students had a family income below the minimum wage, 77.6% had a nuclear family, and 50.3% lived in the city center. Cupping (blood letting 83.8%) was the most frequent CAM practice, and acupuncture (55.9%) was the most common practice for women’s health. Mean score of the students was 111.5 ± 19.1 of 189 points on the CACMAS and 52.7 ± 7.08 points on the Health Perception Scale. No significant correlation was found between the scores of the CACMAS and Health Perception Scale (p > 0.05). Conclusion: Students’ views on traditional complementary medicine and health perceptions were found to be high. It is necessary to increase the awareness of students on these topics.